Bullet train : a novel - Isaka, Kotaro, 1971- (The Overlook Press, 2021)
Lady Bird, an unlucky assassin, is tasked with grabbing a suitcase from a bullet train from Tokyo to Morioka and exiting at the next stop, but doesn't realize other dangerous passengers are trying to do the same.